Application of staphylococcus protein A in the affinity chromatography and immunoadsorption - Святенко, О. В.; Васильченко, О. А.; Васильченко, К. К. (Problems of Environmental Biotechnology, 2013)
Protein A is native or recombinant proteins of microbial origin that bind to mammalian immunoglobulins. In the work characteristics of protein A, affinity sorbents on its basis, advantages of protein A for application as ligands in the affinity chromatography for antibodies purification, extraction of different antibody fractions from blood serum, antibodies and immune complexes from blood plasma of ill people in the process of immunoadsorption.